2020
DOI: 10.1111/jnu.12544
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Butch versus Femme Identity in Body Image and Breast Health Among Lesbians in Taiwan: Results of an Online Survey

Abstract: Purpose The views of butch‐ and femme‐identified lesbians toward their own breasts, breast cancer, breast cancer screenings, and their behavior and intentions toward breast health care were examined and compared in this study. Methods A total of 208 Taiwanese lesbians (134 butch‐identified lesbians and 78 femme‐identified lesbians) completed an online survey. Results Butch‐identified lesbians were more likely to hold negative views regarding their own breasts, which were found to be significantly and negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…As shown in Table 1 , ten measures were used to assess different aspects of body (dis)satisfaction in 11 studies while five studies ( Adams et al, 1993 ; Jensen and Moriarty, 2008 ; Kwan and Lee, 2018 ; Risica et al, 2008 ; Wang et al, 2020 ) used self-developed single-item measures. The most used measure was the Multidimensional Body–Self Relations Questionnaire–Appearance Scales (MBSRQ-AS; Brown et al, 1990 ; Cash, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Table 1 , ten measures were used to assess different aspects of body (dis)satisfaction in 11 studies while five studies ( Adams et al, 1993 ; Jensen and Moriarty, 2008 ; Kwan and Lee, 2018 ; Risica et al, 2008 ; Wang et al, 2020 ) used self-developed single-item measures. The most used measure was the Multidimensional Body–Self Relations Questionnaire–Appearance Scales (MBSRQ-AS; Brown et al, 1990 ; Cash, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly assessed aspects of body (dis)satisfaction were satisfaction with overall physical appearance ( n = 7; Adams et al, 1993 ; Chait et al, 2009 ; Gillen and Markey, 2014 ; Kwan and Lee, 2018 ; Luszczynska et al, 2012 ; Risica et al, 2008 ; Samah and Ahmadian, 2014 ) and overall body areas ( n = 6; Andrew et al, 2016 ; Chait et al, 2009 ; DeMaria et al, 2011 ; Katz et al, 2009 ; Samah and Ahmadian, 2014 ; Swami and Furnham, 2018 ). Few studies examined (dis)satisfaction with specific body areas such as breasts ( Chait et al, 2009 ; Swami and Furnham, 2018 ; Wang et al, 2020 ) and genitals ( DeMaria et al, 2011 ). Other dimensions of body image that are not specific to body (dis)satisfaction, such as body appreciation ( Andrew et al, 2016 ; Ramseyer Winter et al, 2020 ), appearance orientation (the extent to which one invests in their appearance; Chait et al, 2009 ; Gillen and Markey, 2014 ; Samah and Ahmadian, 2014 ), evaluation concerning body weight, size, or shape ( Ludman et al, 2010 ; Samah and Ahmadian, 2014 ), feelings about how one’s body appears to others ( Ramseyer Winter et al, 2020 ; Wang et al, 2020 ), and negative feelings when looking at one’s body ( Jensen and Moriarty, 2008 ), were also examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the number of studies conducted for different genders varied greatly (627 vs. 16), the comparison revealed that male-related research focused more on sexual health (HIV/STI), while female-related research was relatively more concerned with mental health (25.00 vs. 3.35%). Furthermore, four studies investigated breast-related health among female sexual minorities (68)(69)(70)(71), all of which were conducted in Taiwan.…”
Section: Concept Informationmentioning
confidence: 99%